1986
DOI: 10.1177/109019818601300202
|View full text |Cite
|
Sign up to set email alerts
|

Community Intervention to Lower Blood Cholesterol: The "Know Your Cholesterol" Campaign in Pawtucket, Rhode Island

Abstract: Sufficient data exist to support approaches to lowering cardiovascular disease risk which target population-wide reductions in elevated blood cholesterol levels. Within the context of a multifactorial cardiovascular disease prevention program, a 2-month cholesterol education campaign was launched to encourage citizens to "Know Your Cholesterol" by attending screening, counseling, and referral events (SCOREs) held throughout the community. These events featured assessment of dietary fat and cholesterol, rapid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Males and less well educated individuals showed insignificantly greater declines in systolic blood pressure in Pawtucket than in the comparison city. The previously described city differential in body mass index occurred predominantly in males, in those under the age of 35 years, and in those with less education.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Males and less well educated individuals showed insignificantly greater declines in systolic blood pressure in Pawtucket than in the comparison city. The previously described city differential in body mass index occurred predominantly in males, in those under the age of 35 years, and in those with less education.…”
Section: Resultsmentioning
confidence: 90%
“…Further, a number of short-term formative studies conducted simultaneously within the overall project demonstrate the efficacy of cholesterol change, weight control, nutrition, and exercise efforts. [35][36][37][38] Probably the nutrition and weight-control programs were the most effective, judging from the body mass index data. In addition, the possibility that the survey data are themselves inaccurate must be considered.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[45][46][47][48]59,61,64,69,73,76,77,80,81,86,[88][89][90][91][92][93][94] Nineteen of these studies reported a cholesterol reduction. Two of the studies reported no change in cholesterol level following screening.…”
Section: Blood Cholesterol Changementioning
confidence: 99%
“…Screening can falsely reassure people who receive a normal result and therefore no behavioural changes or detrimental behavioural changes are made. 91 This is often referred to as the 'certificate of health' effect.…”
Section: Effects Of Labelling Screening Participants With a 'Sick' Stmentioning
confidence: 99%